Sectoral FDI, Absorptive Capacity and Economic Growth – Empirical Evidence from Egyptian Governorates - Shima'a Hanafy; Marcus Marktanner (Philipps-University Marburg, School of Business and Economics, 2018)
Using a novel panel dataset of Egyptian governorates for the period 1992-2007, we investigate the effects of aggregate and sectoral foreign direct investment (FDI) on Egypt's economic growth. We distinguish between FDI in the manufacturing, agriculture and service sector. The similarity of governorates in terms of institutional characteristics like culture, language, and legal framework and the consistency of the data collection process enables an effective estimation of the effect of FDI on Egypt's economic growth. Employing General Methods of Moments (GMM) panel estimations, we find that neither aggregate nor sectoral FDI has an unconditional effect on economic growth. We also reject human capital as a channel of absorptive capacity, but reveal an interesting effect of FDI in the service sector on economic growth in interaction with domestic private investment (DPI). Service FDI promotes economic growth only if the host governorate has a minimum threshold of DPI to absorb foreign knowledge and technology.
Keywords: F21; F23; F43; O47; O53; 330; foreign direct investment; sectoral FDI; absorptive capacity; economic growth; Egypt